Assistance in dying for older people without a serious medical condition who have a wish to die: a national cross-sectional survey. Issue 2 (13th December 2013) - Raijmakers, Natasja J H; van der Heide, Agnes; Kouwenhoven, Pauline S C; van Thiel, Ghislaine J M W; van Delden, Johannes J M; Rietjens, Judith A C
Abstract : Background: The Dutch euthanasia law regulates physician assistance in dying for patients who are suffering unbearably from a medical condition. We studied the attitudes of the Dutch population to assistance in dying for older persons who have a wish to die without the presence of a serious medical condition. Methods: A cross-sectional survey was conducted among a random sample of the Dutch public (response rate 78%, n=1960), using statements and vignettes about attitudes to assistance in dying for older persons who are tired of living. Results: A minority of 26% agreed with a vignette in which a physician warrants the request for physician-assisted suicide of an older person who is tired of living without having a serious medical condition. Furthermore, 21% agreed with the statement 'In my opinion euthanasia should be allowed for persons who are tired of living without having a serious disease'. People supporting euthanasia for older persons who are tired of living were more likely than opponents to be highly educated (OR 1.6; 95% CI 1.1 to 2.3), to be non-religious (OR 1.7; 95% CI 1.3 to 2.3), to have little trust in physicians (OR 1.6; 95% CI 1.2 to 2.2), and to prefer to make their own healthcare decisions (OR 1.7; 95% CI 1.3 to 2.3). Conclusions: Although it is lower than the level of support for assistance in dying for patients whose suffering is rooted in a serious medical condition, our finding that a substantial minority of the general public supports physician assistance in dying for older people who are tired of living implies that this topic may need to be taken seriously in the debate about end-of-life decision-making.